(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The House has the right to punish its members for their misconduct in the House or outside. In cases of misconduct or contempt committed by the members, the House can impose punishment in the form of admonition, reprimand, withdrawal from the House, suspension from the service of the House, imprisonment and expulsion from the House. The Madhya Pradesh High Court upheld expulsion of two members of the Madhya Pradesh Legislative Assembly observing that since the Legislative Assembly had the power and privilege of expelling a member resulting in the vacation of his seat, the correctness, legality or propriety of the resolutions expelling the concerned members could not be challenged in courts of law.However, the Punjab and Haryana High Court held that a State Legislature was not clothed with any power to expel duly elected members as a measure of punishment for contempt of the House.